Engaging Young Minds in Civic Education With Fun Picture and Picture Activities In Grade IV - Zain, Adibza fawwaz; Iksam; Makmun (Genderang Asa: Journal of Primary Education, 2025)
The primary objective of this research was to evaluate the efficacy of the Picture and Picture cooperative learning paradigm in enhancing the learning outcomes of fourth-grade students in PPKN, with a particular emphasis on their comprehension of the symbolic meanings of Pancasila principles. The researchers implemented a Classroom Action Research (CAR) design encompassing planning, implementation, observation, and reflection phases over two teaching cycles. Students actively learned through collaborative activities during each cycle, including various instructional meetings. Evaluative assessments and observational protocols were implemented to evaluate student advancement. Following the implementation of the Picture and Picture model, the percentage of students meeting the minimum competency standard (KKM) increased from 37.93% in the pre-cycle to 82.75%, indicating a substantial improvement in student learning. The intervention's effectiveness was also evident in the students' improved average scores. These results corroborate the assertion that the Picture and Picture paradigm effectively improves student comprehension of PPKN materials, fostering a more prosperous and interactive learning experience. The implications for future research include examining the long-term retention of knowledge acquired through innovative teaching methods and examining the model's applicability across various subjects and educational levels. Furthermore, educators are encouraged to incorporate this model into their pedagogical practices to improve the quality of students' civic education